2018
DOI: 10.1097/rlu.0000000000002022
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Equivalent of the Hepatic Hot Spot Sign With CT Correlation

Abstract: A 43-year-old woman presented with an FDG-avid mediastinal Ewing sarcoma invading and nearly occluding the superior vena cava. Geographic increased FDG uptake in hepatic segment IVA was the only other site of nonphysiologic FDG activity. This focal activity was without an underlying mass, had atypical morphology for a hepatic metastasis, and correlated well with prior CT findings of abnormal segment IVA enhancement resulting from the recruitment of portocaval collaterals. In the correct setting, the F-FDG hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The third inflow system may cause focal contrast enhancement or radiotracer uptake on imaging, which can be misinterpreted as a neoplastic entity. 7 18 F-FDG uptake in the liver secondary to vascular obstruction is well known [8][9][10]. No vascular obstruction was identified in any of the presented cases.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The third inflow system may cause focal contrast enhancement or radiotracer uptake on imaging, which can be misinterpreted as a neoplastic entity. 7 18 F-FDG uptake in the liver secondary to vascular obstruction is well known [8][9][10]. No vascular obstruction was identified in any of the presented cases.…”
mentioning
confidence: 56%
“…7 18 F-FDG uptake in the liver secondary to vascular obstruction is well known. [8][9][10] No vascular obstruction was identified in any of the presented cases. These cases of artifactual focal hepatic avidity on PSMA PET are useful to raise awareness of their likelihood and their potential to cause image misinterpretation leading to unwanted PCa treatment escalation or denying patients therapy with curative intent.…”
mentioning
confidence: 61%
“…On our PSMA-PET/CT study, an aberrant right gastric vein resulted in focally greater tracer activity in the differentially perfused portions of liver parenchyma. Similarly, in the setting of superior vena cava obstruction, areas of focally increased tracer activity in hepatic segment IV related to venous collateralization via third inflow pathways have been reported on PET studies performed with 18 F-fluorodeoxyglucose (FDG) and pulmonary perfusion scintigraphy studies performed with 99m Tc-macroaggregated albumin [7 , 8] .…”
Section: Discussionmentioning
confidence: 80%
“…4,5 A literature search identified reports of 4 cases of false-positive FDG activity in the same region of the liver in SVCO. 1,[6][7][8] It was suggested that FDG PET study can be repeated using an IV injection site in the FIGURE 1. Above are the cross-sectional PET/CT series and MIP images (on the right) at the level of the liver dome acquired 60 minutes postinjection of FDG activity.…”
mentioning
confidence: 99%
“…This can result in contrast enhancement on CT or focal tracer activity on 99m Tc-sulfur colloid scintigraphy in medial left lobe of the liver near the falciform ligament 4,5 . A literature search identified reports of 4 cases of false-positive FDG activity in the same region of the liver in SVCO 1,6–8 . It was suggested that FDG PET study can be repeated using an IV injection site in the lower extremity 1,7 .…”
mentioning
confidence: 99%